The impact of supply chain security practices on security operational performance among logistics service providers in an emerging economy - Zailani, S.; Subaramaniam, K.S.; Iranmanesh, M.; Shaharudin, M.R. (Emerald, 2015)
Purpose – The security issue in supply chains is among the most pressing concerns that firms are currently facing. As a preliminary attempt to address this lack of empirical research, the primary purpose of this paper is to explore the relationship between security practices and the security operational performance with respect to security culture as a moderator. Design/methodology/approach – With the resource-based view of the firm as the theoretical underpinning, the study utilizes survey data to test the propositions derived from the security literature and partial least squares for the analysis. Findings – The research reveals four crucial practices of supply chain security that collectively affect a firm’s security operational performance among Malaysian service providers. It is also interesting to observe that security culture positively moderates the relationship between facility management and the security operational performance of the firm. Research limitations/implications – Firms in emerging countries need to realize that supply chain security practices can result in significant benefits to their firms that can give them additional incentives to adopt these initiatives. This study may also help policymakers in emerging countries, in general, in setting appropriate policies and strategies, and Malaysia, in particular, for ensuring that it is a secure location for exporting cargo and giving assurance to the local and international investors to continue their investment. Practical implications – This study will assist supply chain managers and logisticians to re-examine their existing supply chain security model by considering the selected supply chain security practices, which have a significant impact on supply chain security operational performance. Individual firms need to strategize their business model with the inclusion of security aspects, which will surely create a competitive advantage over other players in the logistics industry. Firms can develop the best appropriate supply chain security model that will benefit the firm, customers, and business partners, such as suppliers and local authorities. Originality/value – The study highlights is the important role of the supply chain security practices to deliver high quality of service in terms of supply chain security operational performance in emerging countries. In addition, it offers an empirical analysis of the moderating role of security culture on the relationship between supply chain security practices and security operational performance.